Aplikasi aktivitas antioksidan tepung gathot (singkong terfermentasi) dalam edible film sosis ayam di suhu ruang - Astari Ratnaduhita; Adi Magna Patriadi Nuhriawangsa; Lilik Retna Kartikasari (Livestock and Animal Research, 2021)
Objective: The objective of this research is to examine the antioxidant properties of gathot and its potential as edible film.Methods: The materials used were dry gathot, carrageenan, and glycerol. The method was conducted experimentally, antioxidant activities test of gathot flour were analyzed descriptively. Physicochemical test of the chicken sausage was analyzed quantitatively by RAL with a 2x5 factorial pattern. The first factor was the types of edible film (0.00 and 0.75%), and the second factor was storage time (0; 2; 4; 6; 8 days) with seven repetitions each variables. The quantitative data were processed by Minitab 19.0.Results: The results of the antioxidant test of gathot flour were antioxidant activities of 26.174 ppm; scavenging ability of 49.37%; phenol of 4,852.84µg/g; flavonoids of 4,520.30µg/g. The chicken sausage for eight days at room temperature has a decrease in pH value, a* and b*, and an increase in TBA (Thiobarbituric Acid) value and water content.Conclusions: The antioxidant level of gathot flour is classified as a weak antioxidant, the results in the application of gathot flour edible film with a concentration of 0.75% were able to maintain the quality of chicken sausage until day six at room temperature storage (28 ºC).